A comparative study on the attitude and practice of the nursing staffs in urban and rural areas on home visiting - Rosnah S., (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2000)
To assess the attitude and practice of the public health nursing staffs on the home visiting activities based on categories of nursing personnel and level of urbanity.Cross sectional survey using postal structured questionnaire sent to 400 randomly selected public health nursing staffs in June 1998 who were involved in doing home visiting in Malaysia. 4 categories of nursing personnel were involved in the survey: Public Health Nurse (PHN), Staff Nurse (SN), Community Nurse (CN) and Assistant Nurse (AN). Response rate was 84.25 % (337) of which 93.3% (125) are from rural area and 79.7% (212) from urban. There is a significant difference noted between the categories of nursing personnel with p-value <0.05. Eleven types of cases visited were chosen to assess the practice and attitude of the nursing personnel on home visiting. Based on type of cases visited it was noted that there is significant difference between the two samples urban and rural (p<0.05). Means distribution noted higher in rural area compared to urban with p-value <0.05 on type of cases visited: normal pregnancy, high-risk pregnancy, postnatal nursing, malnourished program and elderly. However, there is no significant difference between the two samples on type of cases visited: family planning, child less than 5 years old, children with special needs, elderly and cases discharge from hospital.Based on categories of staffs it was noted that the PHN and SN visited more in highrisk pregnancy, postnatal, children with special needs, malnourished program and elderly cases. While, CN are more concentrating on normal pregnancy cases, family planning and postnatal cases. It also showed that AN visited most of that defaulters and children less than 5 years old. Practice of respondent on home visiting by level of urbanity showed that most of the cases in rural areas had 4-6 visits per case as compared to urban only less than 4 cases with p-value <0.004. There is significant difference on the average time spent to do home visiting: higher in rural areas (>10 hours per weeks ) as compared to urban area. Attitude score of the nursing personnel on home visiting showed that it is better in rural with mode score=10 (43.0%) as compare to urban mode score =5 (75.1 %). All 4 categories of nursing personnel have their role in home visiting. Rural areas has done more home visiting as compared to urban areas. It was supported by the attitude scoring and practice were better in rural as compared with urban.